Pembangunan Kakas Bantu Pengukuran Maintainability pada Tahap Perancangan Perangkat Lunak - Sigit Widodo; Fajar Pradana; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Maintainability is defined as the ease of modifying a system or component of software. Previously there were studies from Kumar and Dhanda in 2015 namely